Review of Islamic Law Regarding Mobile Legend Diamonds as a Wedding Dowry - Muhammad Jahid Lilhaq; Muhibban; Nurhasan; Muhammad Rafi Mudzakky (Al-Mahkamah: Islamic Law Journal, 2024)
This journal reviews Islamic law regarding diamond mobile legends as a wedding dowry. This research aims to find out diamond mobile legends as a dowry from the perspective of Islamic law. This type of research is qualitative research through literature studies in journals and theses. The result of this research is that Mobile Legends diamonds cannot be used as dowry because the top up law in Mobile Legends is that it is not allowed to neglect the player and is against Sharia benefits, whereas according to Sharia law, dowry must be Sharia benefits. In the context of Islamic law, the use of Mobile Legends diamonds as a wedding dowry requires careful consideration. Therefore, the author chose to analyze the title. The law of dowry is obligatory as stated in the Ash-Shafi'i School of thought which defines dowry as something that is obligatory because of marriage or the legal fulfillment of the right to sexual intercourse, because of forced deprivation of the right to sexual intercourse on the part of the husband, or because of khulu' and testimony. So, what is required from men for women is called dowry. Furthermore, the term dowry includes those required because of a valid marriage and those required because of sexual intercourse, whether in a broken, questionable or forced contract. So the meaning of dowry in terms of meaning is more precise than the meaning of dowry according to sharia terms, because the meaning of dowry according to sharia includes what is given to women to justify having sexual relations because of doubts and so on. According to the author, the law on mobile legends diamonds as a wedding dowry is invalid because the mobile legends top up law itself is not permitted because it contains waste and elements of a zero sum game (betting money) while the terms of the dowry are something that is sharia.